Reforming birth registration law in England and Wales? - McCandless, Julie (Reprod Biomed Soc Online, 2017)
The Law Commission of England and Wales is considering what its 13(th) Programme of Law Reform should address. During the consultation process, a project on birth registration law has been mooted. This is a very welcome proposal given that civil birth registration in England and Wales is a compulsory procedure that not only finds its roots in the early Victorian era, but also remains very similar, at least in terms of form and the information that is recorded. I first use two recent legal challenges to illustrate why the current system is coming under increasing pressure. I further use these examples to caution against a law reform agenda that is narrowly focused on the precise information recorded, without a preliminary and wider examination of what the role and purpose of birth registration is, and should be, in society. I argue that this needs to be addressed before the state can justify the parameters of the information recorded. I then use an outline of historical reforms relating to the registration of births outside of marriage to highlight the normative two-parent family model that underpins the birth registration system. I argue that legal reform must be cognizant of the tenacity of this normative family model, particularly in relation to reform proposals surrounding donor conception and the annotation of birth certificates. Finally, I draw attention to wider developments in family law that cast birth registration as a social policy tool for the facilitation of parent–child relationships, particularly unmarried fathers.